Kinetic and Thermodynamic Study of the Activity of AST Analogues Purified From the Blood of Patients with Diabetes Mellitus - Dahir, Jassim Mohammed (American Journal of Bioscience and Clinical Integrity, 2025)
1- The aminotransferase enzyme (AST) activity was measured in the blood of diabetic patients and healthy people. The results showed increased activity of (AST) in patients' blood compared to healthy people. 2- (AST) was purified from the blood of diabetic patients using gel filtration chromatography and Sephadex G-25 filtration gel 3- Two isomers of (AST) were separated from the blood of diabetic patients using ion exchange chromatography and using DEAE-Sephadex X A-50 resin. 4- The kinetic properties of (AST) isomers were studied, and it was found that the isomers are subject to the Michaelis-Menten equation, as the optimal concentration of the basic material (aspartic acid) for each of the isomers was (mole.dm-3 10-3 x 166.5). 5- It was observed that the two analogues obey the Arrhenius equation up to (37) ˚C, and Ea and Q10 were assigned to each of the analogues. 6- The thermodynamic functions of the activity of the amino group transfer enzyme (AST) were calculated through the Van't Hoff and Arrhenius equations for the standard and transition states.